The effect of calf gender on milk lactation traits and lactation gain of Holstein and Simmental cows - Mato Čačić; Zoran Grgić; Marija Špehar; Ante Ivanković (Mljekarstvo)
Considering the challenging market conditions for dairy farms, calf gender management should be one of the tools used to increase profitability. The objective of this paper was to examine the effect of calf gender on lactation milk traits in Holstein and Simmental cows. Holstein cows that calved a female calf had a higher milk yield (p<0.0001) and lower milk fat and protein content (p<0.01) in the first lactation. The favourable effect of female calf on milk yield was also found in the second lactation of Holstein cows (p<0.0001). Simmental cows that calved female calves in the first and the second lactation also had higher milk yield and lactation gain, however the differences were not significant. Although no statistically significant effect of calf gender on milk yield was determined in the Simmental population, indications of positive effect of female calf gender on lactation milk yield impose the need for further research. Using gender selected semen as a tool for calf gender management could enable to increase the milk yield of Holstein cows and the profitability of Holstein farms as well.